Genotoxicity and cytotoxicity of orthodontic bonding adhesives: a review - Riaz Mohammad Adham,; Norma Ab Rahman,; Thirumulu Ponnuraj Kannan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Orthodontic bonding adhesive is one of the integral parts of orthodontic treatment. By means of orthodontic bonding adhesives, different components of fixed orthodontic appliances are attached to the tooth surface. Manufacturers have been introducing various bonding adhesives as there is an increasing demand for orthodontic treatment presently. Focus has been made more on the physical properties of these bonding adhesives rather than their biocompatibility. As orthodontic treatment is a long-time process, the bonding adhesives also remain in close proximity with intra-oral tissues. Therefore, biocompatibility of these adhesives in respect to their genotoxicity and cytotoxicity should be a concern while clinically implicating them. The aim of this review was to provide information about the genotoxicity and cytotoxicity effects of various orthodontic bonding adhesives. An electronic search was conducted across Cochrane, Medline, Web of Science databases, and Google Scholar for literature analysis on the mentioned topic. The studies were reviewed and compared. This article summarizes the results of research studies that have been done to see the genotoxicity and cytotoxicity of orthodontic bonding adhesives. Most research studies summarized in this review article concluded that orthodontic bonding adhesives show some extent of either genotoxicity or cytotoxicity or both. There is still a lack of scientific literature on long-term in vivo studies on the toxic effects of these adhesives. It is advisable to employ several genetic assays and standardized methods for genotoxic evaluation of bonding adhesives through longtime clinical in vivo studies.